Sharia Education as a Moral and Ethical Foundation for Developing a Generation of Character - Huda, Miftahul; Mujino, Mujino; Wala, Wala (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
Islamic education plays a vital role in shaping the character and morality of Indonesia's youth. In the context of an increasingly complex society, Islamic education is expected to serve as a strong moral and ethical foundation for students. However, there are still gaps in the understanding and implementation of Islamic education across various educational institutions. This research aims to explore the role of Islamic education in educating character-driven generations and to identify effective teaching methods in Islamic education. This study employs a qualitative approach, with subjects comprising students, teachers, and parents from several schools in Aceh. Data were collected through in-depth interviews, focus group discussions, and direct classroom observations. Data analysis was conducted using thematic analysis. The findings suggest that Islamic education has a significant impact on shaping students' character, enhancing their social awareness, and strengthening their religious identity. Interactive and contextual teaching methods have proven to be more effective in enhancing students' understanding of Islamic values. Islamic education has excellent potential in educating the youth and forming ethical character. Parental involvement and the relevance of Islamic education to local contexts are also essential factors in the success of this education. This research offers new insights into the role of Islamic education within Indonesia's educational system and is expected to encourage the development of more effective and relevant curricula.Keywords: Islamic Education; Character; Morality; Teaching Methods; Social Awareness